Liver transcriptome analysis and cortisol immune-response modulation in lipopolysaccharide-stimulated in channel catfish (Ictalurus punctatus). Issue 101 (June 2020) - Jiang, Hucheng; Wang, Minghua; Fu, Longlong; Zhong, Liqiang; Liu, Guoxing; Zheng, You; Chen, Xiaohui; Bian, Wenji
Abstract: Channel catfish ( Ictalurus punctatus ) is an important aquaculture species in China. In channel catfish, diseases such as haemorrhagic, sepsis and tail-rot disease are all caused by bacteria as general in China. Most of the pathogenic bacteria are Gram-negative bacteria. Liver transcriptome analysis of the co-injection of cortisol and lipopolysaccharide (LPS) was performed in this study. Preliminary evidence from the results suggest that after the emergence of immune stress, cortisol will up-regulate the complement cascade pathway, down-regulate the coagulation cascade pathway, down-regulate the platelet activation pathway, down-regulate antigen presentation pathway, and show complex regulation relationship to inflammatory factors. At 12 h, the number of differential genes regulated by cortisol was about half less than the number of differential genes regulated by LPS. At 24 h, there was no significant difference between the number of differential genes regulated by cortisol and LPS, but the types of differential genes vary widely. KEGG enrichment analysis found that cortisol regulated LPS-stimulated immune responses mainly focus on cytokines, complement and coagulation cascades pathways, antigen presentation pathways, haematopoiesis, and inflammation. It is suggested that there may be some strategic choice in the regulation of immune response by cortisol. These results will help understand the pathogenesis and host defence system in bacterial disease caused by Gram-negative bacteria. Highlights: Liver of channel catfish ( Ictalurus punctatus ) transcriptome test was used to study the regulation of LPS-induced immune response by cortisol. Cortisol regulates immune responses of LPS-stimulated mainly focus on cytokines, complement and coagulation cascades pathway, antigen presentation pathways, haematopoiesis, and inflammation. Cortisol upregulates the complement alternative pathway at 12 h and negatively regulates it at 24 h. After the immune stress, the regulation of cortisol on immune response maybe choose different regulation strategies over time.